Integration of Health Professional Workstations in Hospital Information Systems - Winter, Alfred; Lagemann, A.; Budig, B.; Grothe, W.; Haux, Reinhold; Herr, S.; Pilz, J.; Sawinski, R.; Schmücker, P. (1996)
Health professionals at a ward need appropriate health professional workstations for being able to get all the information they need. It is the task of the management of a hospital information system (HIS) to provide access to the required information procedures in a uniform way. The paper gives a taxonomy of uniformity but makes clear, that uniform user interfaces are worthless, if there is no appropriate communication infrastructure at both the logical and the physical level of the corresponding HIS. Experiences in the Heidelberg University Hospital show, that pragmatic approaches can be successful.